Analiza kakovosti v ginekološki kirurgiji - Kobal, Borut (Zdravniški vestnik, 2003)
Background. The "Quality Management Project", prepared by the Slovene Medical Chamber, served as the basis for determination of the quality-control indicators for gynecologic surgery. The authors have created a questionnaire that enables the analysis of these indicators. A pilot data entry was carried out between April and October 2001; since January 2002 the data entry has beendone regularly in all departments of obstetrics and gynecology in Slovenia. At the National Congress of Obstetricians and Gynecologists of Slovenia, the analysis of quality-control indicators for gynecologic surgery will be presented and discussed in order to determine the standards of qualitymanagement in this field.
Keywords: Genital Diseases, Female; ginekologija; Ginekološke bolezni; Kakovost zdravstvenega varstva; kirurško zdravljenje; kvaliteta; Quality Of Health Care; Surgery